2012
DOI: 10.1016/j.jvc.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the aging of the mitral valve from human and canine myxomatous degeneration

Abstract: During the course of both canine and human aging, the mitral valve remodels in generally predictable ways. The connection between these aging changes and the morbidity and mortality that accompany pathologic conditions has not been made clear. By exploring work that has investigated the specific valvular changes in both age and disease, with respect to the cells and the extracellular matrix found within the mitral valve, heretofore unexplored connections between age and myxomatous valve disease can be found. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 98 publications
(144 reference statements)
1
37
0
Order By: Relevance
“…2E). Interestingly, our findings of increased mitral valve fibrosis suggest that TLR2-KO mice develops accelerated cardiac aging (38). To check whether this cardiac dysfunction is associated with transdifferentiation of fibroblasts to myofibroblasts, we performed immunohistochemistry using specific antibody against periostin, a marker for myofibroblast.…”
Section: Tlr2 Deficient Mice Hearts Exhibit Increased Fibrosis and Exmentioning
confidence: 97%
“…2E). Interestingly, our findings of increased mitral valve fibrosis suggest that TLR2-KO mice develops accelerated cardiac aging (38). To check whether this cardiac dysfunction is associated with transdifferentiation of fibroblasts to myofibroblasts, we performed immunohistochemistry using specific antibody against periostin, a marker for myofibroblast.…”
Section: Tlr2 Deficient Mice Hearts Exhibit Increased Fibrosis and Exmentioning
confidence: 97%
“…[28] The pathology of myxomatous valves in humans and in dogs includes increased cellularity, disorganization In mvd we see the development of degenerative connective tissue, which manifests itself in excessive stromal destruction and alteration of the valve with loss of collagen organization and accumulation of proteoglycans and glycosaminoglycans in the leaflets and chordae. [25] A study by Hadian et al showed a 10% reduction in total collagen and a 20% reduction in fibrillar collagen content in the myxomatous areas of canine valves with mild to moderate mvd. [31] These alterations are known as mucopolysaccharidioses (mpss), which are characterized by a functional deficiency caused by a genetic mutation of a lysosomal enzyme that acts on the sequential catabolism of glycosaminoglycans.…”
Section: Diagnosismentioning
confidence: 97%
“…[25] A roughened area of the valve on the side where the nodules connect with the ventricular chordae is predisposed to suffer myxomatous degeneration. [25] Risk factors associated with the progression of the disease or death in dogs with mvd include age, gender, intensity of the heart murmur, degree of valve prolapse, degree of mitral regurgitation (mr), degree of left atrial enlargement, severity of eccentric hypertrophy, rupture of chordae tendineae and increasing concentrations of natriuretic peptides. [34] mvd lesions occur gradually and do not show clinical signs at the beginning of the first structural changes.…”
Section: Diagnosismentioning
confidence: 99%
“…1 A leukocytic inflammatory component is distinctly absent. 5 As valvular lesions increase in size, they may interfere with valve competency, resulting in regurgitant flow and secondary myocardial compensatory changes. Endocardiosis is a common age-related lesion in several species, including dogs (canine myxomatous mitral valve disease), pigs, and humans.…”
Section: Introductionmentioning
confidence: 99%